The spectroscopic and transition properties of phosphor selenium: MRCI+Q study including spin-orbit coupling. (January 2021) - Xiao, Lidan; Liu, Yong; Ren, Xiaoying; Yan, Bing
Highlights: MRCI+ Q calculations are performed on PSe with including the spin-orbit coupling. Potential energy curves and spectroscopic constants for bound states of PSe are reported. The radiative lifetimes of the transitions 1/2(2)-X1 1/2, X2 3/2-X1 1/2, 5/2-X2 3/2, 1/2(4)-X1 1/2, 3/2(3)- X1 1/2, 1/2(4)-X2 3/2 and 3/2(3)-X2 3/2 are reported. Abstract: At present, the complete picture for the electronic structure of the PSe is still unclear, particularly for the interactions of excited states. In this paper, a comprehensive computational study on the 27 Λ-S electronic states correlated to the lowest three dissociation limits of PSe is carried out using the multireference configuration interaction method(MRCI) in combination with the Davidson correction (+ Q ) in the calculations. The potential energy curves (PECs) of these states are calculated and the spectroscopic constants of low-lying bound states are obtained, which are in good agreement with previous works. The spin-orbit coupling (SOC) is considered with Breit-Pauli operator via state-interacting technique. The PECs of 18 low-lying Ω states corresponding to the lowest three dissociation limits are investigated. The Λ-S compositions of some Ω states, as wells the transition dipole moments, the Franck–Condon factors and the radiative lifetimes of the 1/2(2)-X1 1/2, X2 3/2-X1 1/2, 5/2-X2 3/2, 1/2(4)-X1 1/2, 3/2(3)-X1 1/2, 1/2(4)-X2 3/2 and 3/2(3)-X2 3/2 transitions have been reported. These results are helpful to understand the spectroscopy and structure of electronic excited states of PSe.